2001
DOI: 10.1007/bf01306612
|View full text |Cite
|
Sign up to set email alerts
|

Phallacidin stains the kinetochore region in the mitotic spindle of the green algaeOedogonium spp.

Abstract: ErratumIn the article "Phallacidin stains the kinetochore region in the mitotic spindle of the green algae Oedogonium spp." by Sampson and Pickett-Heaps (Protoplasma 217: 166-176, 2001) the collective legends for Figs. 1-6 and 8-13 on pages 169 and 171 were incorrect and should read:

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2004
2004
2009
2009

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 0 publications
0
6
0
Order By: Relevance
“…Actin and myosin in the spindle. We and our colleagues have intensively investigated whether actin and myosin could be involved in mitosis (Forer, 1988;Czaban and Forer, 1994;Sampson et al, 1996;Forer and Pickett-Heaps, 1998;Sampson and Pickett-Heaps, 2001;Forer et al, 2003;Forer, 2005, 2007;Fabian et al, 2007a;Forer et al, 2007bForer et al, , 2008. In brief, actin, myosin and other "muscle" proteins are present in spindles (e.g., Fig.…”
Section: Mitosis In Diatomsmentioning
confidence: 99%
“…Actin and myosin in the spindle. We and our colleagues have intensively investigated whether actin and myosin could be involved in mitosis (Forer, 1988;Czaban and Forer, 1994;Sampson et al, 1996;Forer and Pickett-Heaps, 1998;Sampson and Pickett-Heaps, 2001;Forer et al, 2003;Forer, 2005, 2007;Fabian et al, 2007a;Forer et al, 2007bForer et al, , 2008. In brief, actin, myosin and other "muscle" proteins are present in spindles (e.g., Fig.…”
Section: Mitosis In Diatomsmentioning
confidence: 99%
“…As previously discussed (Forer and Pickett-Heaps, 1998;Sampson and Pickett-Heaps, 2001;Sampson et al, 1996), actin is generally considered to be a nonfunctional component of mitotic spindles. However, a number of EM studies show microfilaments amongst the spindle MTs of higher plant (e.g., Forer et al, 1979;Schmit and Lambert, 1988), animal (e.g., Euteneuer et al, 1977;Gabrion et al, 1980) and algal (Pickett-Heaps and Carpenter, 1993) cells.…”
Section: Discussionmentioning
confidence: 93%
“…However, a number of EM studies show microfilaments amongst the spindle MTs of higher plant (e.g., Forer et al, 1979;Schmit and Lambert, 1988), animal (e.g., Euteneuer et al, 1977;Gabrion et al, 1980) and algal (Pickett-Heaps and Carpenter, 1993) cells. Fluorescently labelled phallotoxins have shown actin within spindles of plant sporocytes, plant tissue culture cells and algal cells (Sampson and Pickett-Heaps, 2001). A prominent feature of the majority of these studies is the close association observed between microfilaments and KMTs (Sampson and Pickett-Heaps, 2001).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations